Carbon and silica interlayer influence for the photocatalytic performances of spindle-like α-Fe2O3/Bi2O3p–n heterostructures. (January 2016) - Sun, Lingling; Wu, Wei; Tian, Qingyong; Lei, Mei; Dai, Zhigao; Xiao, Xiangheng; Ren, Feng; Jiang, Changzhong
Abstract: The p–n heterojunction is an effective structure to suppress the recombination of photogenerated charge carriers due to the built-in internal electric field. Herein, we successfully synthesize a spindle-like α-Fe2 O3 /Bi2 O3 core–shell heterostructure, in which α-Fe2 O3 is an n -type semiconductor and Bi2 O3 is a p -type semiconductor. In comparison with pure α-Fe2 O3 seeds, the α-Fe2 O3 /Bi2 O3 p–n heterojunction photocatalyst exhibits tremendous photocatalytic performance on the degradation of Rhodamine B (RhB) under illumination of visible light. In addition, we insert an interlayer between p–n heterostructure, similar to p–i–n heterostructure. The silicon oxide and carbon are selected as the interlayer due to its different conductivity. The as-obtained α-Fe2 O3 /C/Bi2 O3 exhibits higher degradation rate than α-Fe2 O3 /SiO2 /Bi2 O3 . The reason is attributed to the mesoporous structure of carbon layer and its high conductivity so that the photogenerated electrons can be easily transferred from the conduction band of α-Fe2 O3 to the conduction band of Bi2 O3 thereby promoting an effective separation of photogenerated electrons and holes. However, the introduction of interlayer reduces the photocatalytic activity due to the alteration of internal built-in electric field in the heterojunction. We envision that these results have potential applications for designing the heterostructural photocatalysts. Graphical abstract: The spindle-like α-Fe2 O3 /Bi2 O3 core–shell p–n heterojunction has been prepared and it exhibits excellent photocatalytic performance for the degradation of Rhodamine B (RhB) under illumination of visible light. To further understand the mechanism of this p–n heterostructure, carbon and silica are introduced as an interlayer between the p -type and n -type semiconductor.